(untitled) - Guinta, Lawrence R. (New York, 1993)
QFD is a process for listening carefully to what your customers need and then making sure the features they want are designed in during the initial planning for a product--before it's on paper, on the assembly line, or on the shelf. Here is an uncommonly clear and concise explanation of what QFD is all about and how to use it. The authors show how to apply this powerful methodology by using teams creatively to plan efficiently, improve quality drastically and cut costs.
Keywords: Quality function deployment.,Production management,New products; Quality control,Management